2018
DOI: 10.1021/acssuschemeng.8b01482
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Antibacterial Collagen-Based Composite Wound Dressing

Abstract: Collagen is a favorable candidate in the field of biomaterials as a wound dressing. However, it cannot be ignored that the application of collagen is limited to its poor physicochemical and perishable properties. It is significant to endow collagen with antibacterial activity and simultaneously improve its physicochemical properties. Here, we present a simple method to fabricate antibacterial collagen-based wound dressing with appropriate physicochemical properties. First, dialdehyde xanthan gum (DXG) was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 68 publications
4
78
0
Order By: Relevance
“…With regard to the mechanical properties in the dry state, in comparison with our previous work (PGE/SR, σ b = 4.9 MPa, ϵ b = 15.1%), and the other previously reported wound dressings such as collagen/dialdehyde xanthan gum silver nanoparticle composite (Col‐Ag2, σ b = 0.512 MPa, ϵ b ≈ 13%), poly(vinyl alcohol)/chitosan asymmetrical membrane (PVA/CS_10min, σ b = 0.7 MPa, ϵ b = 21%), bilayer chitosan‐gelatin ( σ b = 0.5–1.1 MPa) and electrospun GE mat ( σ b = 1.6 MPa, ϵ b = 17%), the prepared PGE/SR1 bilayer membrane in the present work possessed competitive flexibility, rigidity and toughness, and was capable of protecting dressings from mechanical damage.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…With regard to the mechanical properties in the dry state, in comparison with our previous work (PGE/SR, σ b = 4.9 MPa, ϵ b = 15.1%), and the other previously reported wound dressings such as collagen/dialdehyde xanthan gum silver nanoparticle composite (Col‐Ag2, σ b = 0.512 MPa, ϵ b ≈ 13%), poly(vinyl alcohol)/chitosan asymmetrical membrane (PVA/CS_10min, σ b = 0.7 MPa, ϵ b = 21%), bilayer chitosan‐gelatin ( σ b = 0.5–1.1 MPa) and electrospun GE mat ( σ b = 1.6 MPa, ϵ b = 17%), the prepared PGE/SR1 bilayer membrane in the present work possessed competitive flexibility, rigidity and toughness, and was capable of protecting dressings from mechanical damage.…”
Section: Resultssupporting
confidence: 53%
“…Strikingly, the rest of the prepared membranes showed a reduction in σ b and an increment in ϵ b compared to the corresponding membranes in the dry state. This phenomenon can probably be attributed to the presence of water molecules in the wet GE‐containing membranes, acting as a plasticizer . In particular, the PGE/SR1 (wet state) exhibited a balanced σ b (0.6 MPa) and ϵ b (48.0%) compared with the other membranes.…”
Section: Resultsmentioning
confidence: 97%
“…Hence, intermolecular crosslinking was sought to modify the collagen scaffold’s mechanical strength and to preserve its stability, thus correcting such limitation [ 15 ]. Studies showed that collagen scaffold crosslinked with genipin have a better mechanical profile without having its porosity properties affected and have minimal toxicity [ 48 ]. This synergistic improvement suggests good chemical compatibility between the two phases, as well as good dispersion [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It therefore makes sense that the present work provides a viable avenue to tune the gelatin hybrid from soft (hard) to hard (soft). In comparison with the previously reported biopolymer‐based wound dressing scaffolds (dry state) such as collagen bio‐artificial dermis ( σ b = 1.5 MPa), collagen/dialdehyde xanthan gum‐silver nanoparticles composite (Col‐Ag2, σ b = 0.512 MPa, ϵ b ≈ 13%), electrospun gelatin mat ( δ = 1.6 MPa, ϵ = 17%) and porous gelatin scaffolds (Gf‐2.0, δ = 7.8 kPa), the P1G1‐GE membrane ( δ = 6.1 MPa, ϵ = 9.4%) described here possessed appropriate rigidity and flexibility, which allowed the dressings to fit well in the wound sites.…”
Section: Resultsmentioning
confidence: 77%